Mental Models in Chemistry: Prospective Chemistry Teachers’ Mental Models of Chemical Equilibrium - Kelly Sinaga (JPPS (Jurnal Penelitian Pendidikan Sains), 2022)
In this study, we described research into prospective chemistry teachers' mental models for chemical equilibrium. This research aimed to describe the profile of prospective chemistry teachers' mental models of chemical equilibrium. This study was held at one university in Tangerang. The subjects in this study were 22 students. The method used is the descriptive research method, using diagnostic tests as a research instrument. The research outcome showed 59.42% for the macroscopic stage, 51.34% sub-microscopic stage, and 66.18% symbolic stage. This outcome showed the variety of the understanding of prospective chemistry teachers for every level of chemical representation but generally, the understanding at the submicroscopic level was still relatively low. The profile of the mental models at each level of representation showed varied results but on average has a higher percentage in the Phenomenon Model and the Character-Symbol Model.  The category of mental models at each level of representation mainly shows a linkage between the characteristic of the level of representation and the students’ mental model type. The result of this work point to the need of developing a learning strategy that accommodates the multiple representations. The next study also should recognize that sub-microscopic level representation is very important as this level help the students understand the scientific concept and give the correct explanation to chemical phenomena and reduce the misconception.